Pengaruh Bimbingan Orang Tua Terhadap Motivasi Belajar selama Proses Pembelajaran Daring Pada Siswa Kelas V SDN 101 Makale 4 - Irene Hendrika Ramopoly; Charlie Baka; Jelsi Jelitri Anton (Jurnal Keguruan dan Ilmu Pendidikan, 2022)
The purpose of this study was to determine whether there was an influence of parental guidance on learning motivation during the online learning process in fifth grade students of SDN 101 Makale 4. Quantitative research was used in this study using expost facto research and the sample consisted of 19 students taken from the whole population.Questionnaire were used in collecting data which became the measuring instrument for each variable. The questionnaire instrument distributed to respondents, previously tested, including validity and reliability test. Simple linear regression analysis was used in data analysis. From the results of the study, it can be seen that there is an influence of parental guidance on learning motivation during the online learning process in fifth grade students of SDN 101 Makale 4. This is obtained from a significant value of 0.042 > 0.05 and the determination of R Square = 0.222 which means that the influence of parental guidance on motivation learning during the online learning process is 22.2%.